Tycoon's unexpected Caribbean fling - Hayes, Ella (Harlequin Romance, 2021)
"Billionaire Joel Larsson is no stranger to the spotlight. But when his engagement implodes, all Joel wants is to get away. Cue a solo trip to a private Caribbean island! Yet, when he comes face-to-face with Emilie Clayton--Joel's far-too-beautiful personal chef--things get complicated... Joel may be tempted to open the door to a fling with Emilie--but is he strong enough to keep his heart locked away?"--back cover.